The Strategy Development of SMEs Metal - Gunawan, Diah Setyorini; Widayaningsih, Neni; Barokatuminalloh, Barokatuminalloh (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
This research aimed to identify the profile of SMEs metal and to analyze the predictors that differentiate the performance achievement of metalworkers in Pasir Wetan Village, Karanglewas Sub-District, Banyumas Regency using primary data obtained from direct interviews with metalworkers in Pasir Wetan Village, Karanglewas Sub-District, Banyumas Regency. Primary data included the data of net income rate, the amount of labor used, the amount of bank credit received, business duration, education level, and the amount of production. The data were analyzed using descriptive analysis and discriminant analysis. The analysis results indicated that the increase in the amount of production and the amount of labor used were the predictors that differentiate the revenue achievement between superior metalworkers group and non-superior metalworkers group. In addition, the amount of production was the best predictor to differentiate the revenue achievement between superior metalworkers group and non-superiors metalworker group.